GREEN TEA EXTRACT IN AN EYELASH GROWTH ENHANCER GEL FORMULATION: STABILITY TEST, EYE IRRITATION TEST, AND HUMAN EYELASH GROWTH ACTIVITY - Roes Lie, Indra Syahputra; Djajadisastra, Joshita; Saputri, Fadlina Chany (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To formulate a green tea extract (GTE), which is often used as a hair growth product, to produce an eyelash gel with good stability, effectiveness, and safety for growing eyelashes. Methods: GTE was formulated into a gel. A stability test was performed at a high temperature (40±2°C), room temperature (25±2°C), low temperature (4±2°C), and a cycling temperature. An in vitro hen's egg test-chorioallantoic membrane assay was performed to evaluate potential eye irritation. An eyelash growth test was conducted by length measurement using an eyelash ruler before and after 2 mo of application in human volunteers. Results: The GTE gel was stable in storage at high, room, and low temperatures and at cycling temperatures and did not cause eye irritation. Eyelashes grew significantly more in the test group than in the placebo group after 2 mo of application (p<0.05). Conclusion: GTE gel provides a new, safe, and effective option for growing natural eyelashes.